2017
DOI: 10.1111/1753-0407.12559
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Chinese herbal medicine Jinlida in type 2 diabetes patients based on stratification: Results of subgroup analysis from a 12‐week trial

Abstract: Jinlida significantly improved glycemic control, with greater improvements in patients with poor glycemic control and male, elderly, of normal weight, or with a long disease course. Furthermore, Jinlida alleviated insulin resistance with hyperinsulinemia and promoted insulin secretion with hypoinsulinemia. These results need to be further confirmed in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…In the Song Dynasty, Tai Ping Hui Min He Ji Ju Fang , an official traditional Chinese medicine book, recorded the treatment of Xiaoke disease with ginseng. Many of the proprietary Chinese medicines approved by the Chinese government for the treatment of diabetes contain ginsenosides, such as Tianqi Capsule (Pang et al, 2017 ), Jinlida Granule (Tian et al, 2018 ), and ShenMai Injection (Zhang et al, 2008 ).…”
Section: The History Of Ginsengmentioning
confidence: 99%
“…In the Song Dynasty, Tai Ping Hui Min He Ji Ju Fang , an official traditional Chinese medicine book, recorded the treatment of Xiaoke disease with ginseng. Many of the proprietary Chinese medicines approved by the Chinese government for the treatment of diabetes contain ginsenosides, such as Tianqi Capsule (Pang et al, 2017 ), Jinlida Granule (Tian et al, 2018 ), and ShenMai Injection (Zhang et al, 2008 ).…”
Section: The History Of Ginsengmentioning
confidence: 99%
“…Jinlida granule, a traditional Chinese medicine including 17 medicinal components ( Table 1 ), is used for the treatment of T2DM. Lots of studies have shown that Jinlida granules could improve insulin resistance, promote insulin secretion, and reduce blood lipids [ 14 – 17 ]. It has been approved by the China Food and Drug Administration for the treatment of T2DM.…”
Section: Introductionmentioning
confidence: 99%
“… [27] Moreover, the Jinlida granule was verified that it could significantly improve glycemic control, alleviate insulin resistance, and promote insulin secretion, with greater improvements in patients with a long disease course. [28] A previous study demonstrated that Jinqijiangtang tablets could improve T2DM insulin resistance, regulating the gut microbiota and promoting the production of SCFAs. The mechanism was related to increasing the gut barrier function and reducing the host inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%